Scorpion Sting Envenomation - Lakhkar, Bhavana Bhushan; Patil, M.M.; Patil, S.V. (Journal of Nepal Paediatric Society, 2017)
Scorpion sting envenomation is very common problem in rural India especially where the climate is hot and dry. Management techniques have improved tremendously over the time leading to reduced morbidity and mortality. Mortality is mainly when ignorant patients go to the traditional faith healers (Tantrics) and come late to the facility where better management is available. Indian red scorpion (Mesobhuthustamulus) is the main species in India. Autonomic storm caused by venom acting on sodium gated and other channels is the main cause of manifestations in a scorpion sting victim. Cardio-myopathy is the main cause for morbidity and mortality. Many grading systems have been suggested for categorizing and simplifying the treatment. The mainstay of treatment where systemic involvement is there are alpha-1 blocker Prazosin hydrochloride, Fluids and newly arrived purified anti-venom. Scorpion envenomation being a problem of rural remote areas and most patients being from lower socio-economic status, anti-venom use is limited. Hence the treatment of choice remains Prazosin hydrochloride. Risk factors, peculiarities of presentation and dose titration of Prazosin based on severity will be discussed as per personal experience and literature review. J Nepal Paediatr Soc 2016;36(3):284-287